A rare case of cutaneous apocrine adenocarcinoma on the axilla that metastasized to the cervical lymph node 12 years after surgery. Issue 6 (27th August 2020) - Kado, Soichiro; Kamiya, Koji; Maekawa, Takeo; Komine, Mayumi; Murata, Satoru; Ohtsuki, Mamitaro
Abstract : Apocrine adenocarcinoma is a rare malignant neoplasm arising mostly in apocrine‐dense regions. Local recurrence and locoregional nodal metastasis are often observed, and most patients relapse at regional lymph nodes within 5 years. Here, we report a very rare case of cutaneous apocrine adenocarcinoma that metastasized to the lymph node more than 10 years after surgery.